2016
DOI: 10.1016/j.cct.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

A bstinence R einforcement T herapy (ART) for rural veterans: Methodology for an mHealth smoking cessation intervention

Abstract: Introduction Smoking is the most preventable cause of morbidity and mortality in U.S. veterans. Rural veterans in particular have elevated risk for smoking and smoking-related illness. However, these veterans underutilize smoking cessation treatment, which suggests that interventions for rural veterans should optimize efficacy and reach. Objective The primary goal of the current study is to evaluate the effectiveness of an intervention that combines evidenced based treatment for smoking cessation with smart-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…These eight trials started recruitment between 2011 and 2014. Of these trials, one included dyads of patients and caregivers (Van Houtven et al, 2014), four targeted cardiovascular disease risk factors including obesity and hypertension (Jackson et al, 2016;Oddone et al, 2017;Voils et al, 2014;Voils et al, 2016;Zullig et al, 2014;Zullig et al, 2015), one addressed smoking cessation (Wilson et al, 2016), one addressed emergency department follow-up (Hastings et al, 2014), and one addressed osteoarthritis of the knee and hip (Allen et al, 2012; Table 1). The mean participant age was 57.7 years for women and 65.9 years for men.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These eight trials started recruitment between 2011 and 2014. Of these trials, one included dyads of patients and caregivers (Van Houtven et al, 2014), four targeted cardiovascular disease risk factors including obesity and hypertension (Jackson et al, 2016;Oddone et al, 2017;Voils et al, 2014;Voils et al, 2016;Zullig et al, 2014;Zullig et al, 2015), one addressed smoking cessation (Wilson et al, 2016), one addressed emergency department follow-up (Hastings et al, 2014), and one addressed osteoarthritis of the knee and hip (Allen et al, 2012; Table 1). The mean participant age was 57.7 years for women and 65.9 years for men.…”
Section: Resultsmentioning
confidence: 99%
“…In doing so, we found that the proportion of women ranged from 5.1% to 13.3% at the initial data pull, 4.4%-11.7% for mailed recruitment letters, 4.4%-19.2% during attempted to contact for screening, 3.3%-22.0% of those consented, and 3.3%-22.2% of those participants who completed the final outcome assessment. Five studies consented more than 10% women (Hastings et al, 2014;Oddone et al, 2017;Voils et al, 2014;Wilson et al, 2016;Zullig et al, 2014), and all but one of those targeted conditions that are not inherently tied to the patient's age (e.g., smoking, obesity, inactivity, or emergency department use). The one study that did target age-related conditions, specifically hypertension and hyperlipidemia, also aimed to increase recruitment of women (Zullig et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations